Effect of intermittent high altitude hypoxia on the structure and enzymatic activity of cardiac myosin - Pelouch, V; Ostádal, B; Urbanová, D; Procházka, J; Ressl, J; Widimský, J (Physiologia Bohemoslovaca, 1980)
The time course of structural and enzymatic changes in cardiac myosin was studied in the right and left ventricle of rats exposed to intermittent high altitude (IHA) hypoxia. In the controls, ATPase activity and myosin structure in both ventricles was the same. After the third exposure to simulated high altitude (2 600 m), myosin enzymatic activity rose significantly in the left ventricle and a significant right-left difference appeared. In the next phase of adaptation (11 exposures, 6 000 m), myosin ATPase activity fell in both ventricles and the right-left difference disappeared. After the 16th exposure (7 000 m), enzymatic activity increased again in both ventricles and attained control values. IHA also produced significant structural changes in cardiac myosin, particularly in the rigaht ventricle. The changes were characterized by the formation of myosin aggregates with significantly lower ATPase activity that the myosin monomer. The time course and localization of structural and enzymatic changes in cardiac myosin corresponded to the morphological damage to the heart fibres.
Keywords: chromatografie iontoměničová; adenosintrifosfatasy; Adaptation, Physiological; krysa rodu Rattus; Hypoxia; zvířata; Chromatography, DEAE-Cellulose; hypoxie; atmosférický tlak; Adenosine Triphosphatases; Male; Altitude; Chromatography, Ion Exchange; fyziologická adaptace; Myosins; myosiny; Rats; myokard; Atmospheric Pressure; Animals; Myocardium; mužské pohlaví; chromatografie DEAE-celulózová; nadmořská výška